Kepuasan kerja karyawan bagian rekam medis pada RSUD Blambangan - Nilawati, Wardha (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The success of a hospital in carrying out its functions is marked by the excellent service quality of the hospital. To optimize existing human resources, the thing that needs to be considered is the provision of workloads for each employee to match their portion. The purpose of this study was to determine the effect of workload and on job satisfaction of employees of the Medical Record Section at Blambangan Hospital Banyuwang. This study uses a quantitative approach. The number of samples used were 35 respondents who worked at the Blambangan Hospital, especially in the medical record section. Data collection techniques using interviews, questionnaires, and observations. Then, the data obtained were processed by simple regression analysis. The results showed that the effect of workload on employee job satisfaction was 77.1%. This indicates that if employee job satisfaction is considered properly, it will lead to a sense of satisfaction at work